My Diabetes My Way: clinical outcomes impact and user experiences for an electronic personal health record for diabetes. (2019) - Cunningham, Scott; Pokrajac, Ana; Allardice, Brian; Brillante, Massimo; Wilson, Lyn; Wake, Debbie
No abstract available